Second Harmonic Generation Circular Dichroism from Self‐Ordered Hybrid Plasmonic–Photonic Nanosurfaces. Issue 3 (6th December 2013) - Belardini, Alessandro; Benedetti, Alessio; Centini, Marco; Leahu, Grigore; Mura, Francesco; Sennato, Simona; Sibilia, Concita; Robbiano, Valentina; Giordano, Maria Caterina; Martella, Christian; Comoretto, Davide; de Mongeot, Francesco Buatier
<x xml:space="preserve">Abstract</x> Hybrid structures composed by self‐ordered dielectric nanospheres and partially covered by gold nanocrescents, produce efficient second harmonic generation signals due to the cooperative effect of localized plasmon excitation and 2D Bragg gratings. Asymmetries in the geometric shape of the gold nanocrescents induce a circularly polarized optical response. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>